Optimization of carboxymetyhlcellulase and polyoses production from oil palm empty fruit bunch fermentation by Trichoderma Virens - Nurrazean Haireen Mohd. Tumpang, 1987-; Madihah Md. Salleh, supervisor; Fakulti Biosains Dan Kejuruteraan Perubatan (2012)
Thesis (Sarjana Sains (Biosains)) - Universiti Teknologi Malaysia, 2012